The Constraints School Toward Good Local Governance: Local Governments of the Philippines Circa 2001—2010 - Javier, Aser B. (Silliman Journal, 2022)
This paper aims to account the constraints school that emerged in the local governments of the Philippines from the period 2001- 2010. The constraints school argues that changes in the external landscape represented by national institutional indiscretion limits the internal landscape that local actors must deal with. This paper argues that the national tradition of governance shapes and influences local institutional factors and holds the key to the constraints school toward good local governance in the Philippines. It does so by examining the national-local experience and the interactions among these factors through three cases. The study found out that a three-level dynamics influences the shape of local institutions. The first level dynamics refers to the national formal normative orientations that characterize the national government as a political institution that influences local governments. Second is the local government's capacity that structure local actions towards dependency. The third refers to the politics-corporate balance of local government policy on decentralization. This paper concludes that the evolution of the constraints school implicitly establishes the outcomes of the current local governance in the Philippines as an unintended consequence of the national practice of decentralization throughout the nineyear period.